Biological sensitivity to context: A test of the hypothesized U-shaped relation between early adversity and stress responsivity. (May 2020) - Shakiba, Nila; Ellis, Bruce J.; Bush, Nicole R.; Boyce, W. Thomas
Abstract: We conducted signal detection analyses to test for curvilinear, U-shaped relations between early experiences of adversity and heightened physiological responses to challenge, as proposed by biological sensitivity to context theory. Based on analysis of an ethnically diverse sample of 338 kindergarten children (4–6 years old) and their families, we identified levels and types of adversity that, singly and interactively, predicted high (top 25%) and low (bottom 25%) rates of stress reactivity. The results offered support for the hypothesized U-shaped curve and conceptually replicated and extended the work of Ellis, Essex, and Boyce (2005). Across both sympathetic and adrenocortical systems, a disproportionate number of children growing up under conditions characterized by either low or high adversity (as indexed by restrictive parenting, family stress, and family economic condition) displayed heightened stress reactivity, compared with peers growing up under conditions of moderate adversity. Finally, as hypothesized by the adaptive calibration model, a disproportionate number of children who experienced exceptionally stressful family conditions displayed blunted cortisol reactivity to stress.